Case of congenital Langerhans cells histiocytosis in an infant - T. T. Valiev; L. A. Makhonova; A. M. Kovrigina; E. N. Sholokhova; N. N. Tupitsyn; I. N. Serebryakova; G. L. Mentkevich (Онкогематология, 2014)
In this article a rare case of monosystem form of congenital Langerhans cells histiocytosis (LCH) in 3 weeks of age girl was described. Local lesion of oral mucosa of the infant with LCH was first described. Morphological, immunological and clinical features of this rare disease have been characterized. Authors concluded that timely diagnostics is very important to risk-adapted therapy at children with LCH.